(untitled) (Research, Society and Development, 2020)
The Caeté River Basin, located in the northeastern mesoregion of the State of Pará, has a large number of available plant species, being used by residents of the riverside communities, however, many plants have not yet been identified or registered the traditional uses. This article aimed to characterize the therapeutic uses of "Insulin" Cissus verticillata (L.) Nicholson & C. E. Jarvis in the Ponta de Urumajó Community - PA, verifying its effectiveness for the treatment of Diabetes mellitus. The research is based on a qualitative methodological approach, through field research, using as techniques of data collection the application of free listing, interviews with key informants, application of forms, collection of plant samples, observation, recording video and photos. Results point out that the community of Ponta do Urumajó demonstrates a great framework of knowledge about medicinal plants, using them in the most diverse ways, besides, of course, knowing the practices used for the use of the species that will be used for health care. The community has widely used the use of Cissus verticilata, unaware of its toxic effects and the dangers of adverse reactions. To that end, this work tends to contribute to the recognition and valorization of the local knowledge and practices of traditional peoples of the Amazon and seeks an integration between scientific and traditional knowledge for the consolidation of species conservation practices, in addition to observing the active principles present in the plant, its toxicity and point out ways for phytochemical studies in the production of a herbal medicine that contains the chemical content of C. verticillata, giving quality of life to diabetic patients.